Developing statewide remdesivir use criteria. (18th February 2021) - Fox, Erin R; Shah, Mark; Vinik, Russell; Brown, Sam; Buckel, Whitney; Webb, Brandon; Zarndt, Janet; Evans, Megan; Mesdaghi, Pejman; Imlay, Hannah N; Spivak, Emily S
Abstract: Purpose: This report describes our process of 4 health systems coming together to agree on standard use criteria for remdesivir as a coronavirus disease 2019 (COVID-19) treatment for patients in Utah. We hope our process provides a framework for remdesivir use in other states and insights on future use of other therapeutic agents that may also be in short supply, such as vaccines and monoclonal antibodies. Summary: Emergency use authorization (EUA) criteria for COVID-19 treatments often allow for broad use of a treatment relative to limited supplies. Without national criteria, each health system must develop further rationing criteria. Health systems in Utah worked together as part of the state's crisis standards of care workgroup to develop a framework for how to limit the EUA criteria for remdesivir to match available supplies. The 4 largest health systems were represented by infectious diseases specialists, chief medical officers, and pharmacists. The group met several times online and communicated via email over a 9-day period to develop the criteria. The clinicians agreed to use this framework to develop criteria for future therapeutics such as monoclonal antibodies. Conclusion: The unique collaboration of the 4 health systems in Utah led to statewide criteria for use of remdesivir for patients with COVID-19, ensuring similar access to this limited resource for all patients in Utah.